Research on the Influence of TikTok Content to Improve Student Achievement in Writing Narrative Texts - Meylina, Meylina; Rahmiaty, Rahmiaty (Faculty of Education Universitas Negeri Malang, 2023)
This study aims to determine the effect of using short TikTok videos on students' abilities in writing narrative texts and to know teachers’ perception on the use of TikTok as teaching media. This article used mixed research methods. Quantitative data were obtained using experimental research, while qualitative data used qualitative descriptive research. The population of this study was class VII students of SMP Negeri 3 Langsa for the 2021/2022 academic year, with a total of 48 students. They were divided into two groups: 24 students in the experimental group were taught through TikTok content, while 24 students in the control group were taught through conventional methods. This study used a written test as a tool. The t-test formula from SPSS 26 was used to assess the data. Then at a significance level of 0.025 and degrees of freedom (df) of (48), observations show that (3.12 > 2.01) was more significant than t-table (2.01). The findings show that the research hypothesis was correct. TikTok was found as an interactive learning media that can represent what the teacher cannot convey and the learning process will be more effective and efficient. It was also an excellent learning medium because there was a mix of various music, pictures and interesting features so that it was not boring for students. Learning media like this can support student learning in writing narrative texts. Thus, this shows that short TikTok content greatly influences students' writing achievement